Biased Credibility and Sharing of Fake News on Social Media: Considering Peer Context and Self-Objectivity State. Issue 4 (2nd October 2021) - Turel, Ofir; Osatuyi, Babajide
ABSTRACT: Several studies have examined the consumption and spread of fake news on social media. Two notable gaps, though, exist in the extant literature. First, prior research has focused on the political orientation of users while ignoring the broader context of sharing, namely the perceived political orientation of their social media peers. Second, there is limited insight about how user states, especially those related to their judgment abilities, influence the critical evaluation of fake news on social media. This paper addresses these gaps by theorizing the roles of perceived peer political orientation and self-objectivity states of users in translating biased credibility assessments of fake news into biased sharing intentions. It reports on an 7experiment (n=408) that primed self-perceived objectivity (a state) in half of the participants to examine its efficacy in moderating the influence of credibility bias (the extent to which users believe the news that highlight ideas that are consistent with their political orientation more than fake news articles that highlight ideas that are inconsistent with their political orientation) on sharing bias (the extent to which they are likely to share fake news that highlight ideas that are consistent with their political orientation more than fake news that highlight ideas that are inconsistent with their political orientation) while accounting for the moderating effect of perceived peer political orientation (a contextual factor). We found that consistency of fake news with people's political orientation increased credibility bias and sharing bias and that credibility bias increased sharing bias. We also found that perceived alignment between a user and their peers' political orientation, as a social context, reduced the effect of credibility bias on sharing bias. Finally, we found mixed support for the moderating effects of primed self-objectivity on the influence of credibility bias on sharing bias; it affected only liberal-leaning participants.